Flower Initiation, Morphology, and Developmental Stages of Flowering-Fruiting of Mindi - Dida Syamsuwida; Endah Retno Palupi; Iskandar Zulkarnaen Siregar; Andry Indrawan (Institut Pertanian Bogor (IPB University), 2012)
The study was aimed to determine flower initiation, floral morphology and to observe the stages of flowering and fruit development of mindi (Melia azedarch L) within a population for one period of time 2008–2009. The methods used were observing directly over the trees and some vegetatives and generatives buds were sampled for dissecting. The observation revealed that the inflorescence type of mindi was panicle, located at the end of a branch. The number of flower varied among inflorescences, ranged between 30–80 that bloomed simultaneously. The flower was hermaphroditic with position of anther was closed to stigma that selfing might be happened. Usually, the ovary contained 5 ovules that developed into seeds. Reproductive cycle was proceeded for 6–7 months within the year, first observation commenced from flower initiation that occur in August, generative buds to flower burst in September–October. Early fruits were formed in October–November and fruits reached physiological-maturity in January–February. Reproductive success was 34%, indicated that the rate of fertilized ovules proportion to be potencially viable seeds were relatively low.